Pertumbuhan dan Hasil Tanaman Jagung yang Ditumpangsarikan dengan Calopogonium caeruleum Hemsl. disertai Pemupukan Nitrogen - B. H. Tampubolon (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
aim of this study was to recognize the influence of CaloDogonium caeruleum aged 24 months or residue of its mulch and the nitrogen fertilizing on the growth and yield of corn plants, the suppression of weed growth as well as biology and chemistry characteristics of soil. The field experiment was carried out in IPB Experiment Field in Darmaga, Bogor. The treatments comprised legume and nitrogen fertilizing factors. The legumes consisted of 3 elements, namely, without legume C. caeruleum. and its mulch residue. There were 4 dosages of nitrogen fertilizing,' 0, 60, 120 and 180 kg N/ha. The design used were Randomized Block Design, 3 replications, experiment plot size 5 x 4 m. The Arjuna variety of corn were planted with minimum tillage system. The weeds growing in the plot without legumes and the one with C. caeruleum residue were killed by using herbiside. Dosage of 44 kg P and 83 kg K fer ha were applied as the basis fertilizers. The corn planting space was 100 x 25 cm one plant/hole. At planting time / dosage of Urea was applied and the rest of it at 30 days later. The result of the experiment revealed that the C. caeruleum treatment suppressed the growth of the weeds, increased the plant height, stalk twist, leaf area index, plant dry-weight, the weight of grain/ear and the dried grain/plot. The plot without legumes, the one with C. caeruleum and the residue of C. caeruleumproduced 5.14,8.65 and 6.25 kg dried grain respectively. The nitrogen fertilizing had no significance effect towards the grain dry-weight. Compared to the treatment without legumes, C. caeruleum treatment increased the population of soil fungi 77%, Nitrosomonas bacteria 120% and soil respiration 82%. There was also an increase of soil organic content, N-total, available P and available K as much as 35%, 30%, 11 % and 6% respectively. Key words: Corn, Caloeogonium caeruleum. Intercropping, Nitrogen fertilizing